The Impact of Postoperative CT Parameters on Functional Outcomes in Joint Depression-Type Calcaneal Fractures Fixed with Sinus Tarsi Locking Plate: A Retrospective Analysis - Chongmuenwai, Adisorn; Polpanich, Nuttakitta; Choovongkomol, Kongtush (Journal of Southeast Asian Orthopaedics, 2025)
Purpose: To examine the correlation between postoperative computed tomography (CT) parameters and functional outcomes in patients treated with sinus tarsi locking plates for joint depression-type calcaneal fractures. Methods: This study retrospectively analyzed patients who underwent sinus tarsi locking plate fixation for joint depression-type calcaneal fractures at a tertiary hospital between 2019 and 2021. The patients were followed up for an average of 16 months. Collected data included demographic information and postoperative CT parameters, including Böhler’s angle and posterior facet congruity. Functional outcomes were evaluated using the Foot and Ankle Ability Measure (FAAM) score. Results: Postoperative CT scans were used to evaluate the quality of fracture reduction in 55 patients with calcaneal fractures treated with sinus tarsi locking plates. The mean FAAM score was 79.4 (range: 42–100). Among the patients, 45 (82%) achieved good functional outcomes, while 10 (18%) had poor outcomes, with no significant demographic differences between groups. Anatomical, near-anatomical, and poor reduction of the posterior facet were observed in 49%, 31%, and 20% of cases, respectively. Böhler’s angle was >20º and <20º in 76% and 24% of cases, respectively. Anatomical reduction of the posterior facet showed a significant correlation (P=0.025) with favorable outcomes, whereas Böhler’s angle showed no significant association (P=0.685). Conclusions: Sinus tarsi locking plate fixation is effective in achieving satisfactory posterior facet reduction and functional outcomes for joint depression-type calcaneal fractures. Postoperative CT scans can help predict functional recovery by evaluating posterior facet reduction. Achieving posterior facet anatomical reduction is essential for favorable functional recovery.